(untitled) - Lazaraton, Anne (New York, 2002)
Language testers have generally come to recognize the limitations of traditional statistical methods for validating oral language tests. They have begun to consider more innovative approaches to test validation, approaches that promise to illuminate the assessment process itself, rather than just assessment outcomes (i.e., ratings). One such approach is conversation analysis (or CA), a rigorous empirical methodology developed by sociologists, which employs inductive methods in order to discover and describe the recurrent, systematic properties of conversation, including sequential organization, turntaking, repair, preference structure, and topic management. CA offers a systematic approach for analyzing spoken interaction from a qualitative perspective, allowing one to make observations about a stretch of talk while at the same time interacting with it. This book aims to provide language testers with a background in the conversation analytic framework and a fuller understanding of what is entailed in using conversation analysis in the specific context of oral language test validation.
Keywords: English language,Conversation analysis,Language and languages; Spoken English,Study and teaching,Foreign speakers,Examinations,Evaluation